Evaluating the competitiveness of leading coffee-producing nations: A comparative advantage analysis across coffee product categories - Ma’ruf Muhammad Imam; Ngo Duong Minh; Bacsi Zsuzsanna; Bozsik Norbert (Open Agriculture, 2025)
This study evaluates the competitiveness of 12 leading coffee-producing nations – Brazil, Colombia, Ethiopia, Guatemala, Honduras, India, Indonesia, Mexico, Nicaragua, Peru, Uganda, and Vietnam – by analyzing their comparative advantages across five product categories: (1) green coffee (excluding roasted/decaffeinated), (2) decaffeinated coffee (excluding roasted), (3) roasted coffee (excluding decaffeinated), (4) roasted and decaffeinated coffee, and (5) coffee by-products (husks, skins, substitutes). Using trade data from 2001 to 2021 (UN Comtrade, HS codes 090111–090122), we employ three quantitative indices: revealed comparative advantage (RCA), relative import advantage (RMA), and relative trade advantage (RTA). The RCA identifies export competitiveness, the RMA assesses import reliance, and the RTA combines both to measure net trade performance. Thresholds of >1 (RCA/RMA) and >0 (RTA) indicate competitiveness. The findings reveal that most countries (10 of 12) exhibit strong competitiveness in green coffee exports (HS 090111), except India and Nicaragua. Mexico and Vietnam show emerging advantages in decaffeinated coffee (HS 090112), but no nation competes in roasted coffee or by-products. This pattern reflects structural constraints in downstream processing, validated through robustness checks comparing RTA trends across sub-periods. The study underscores the need for policies to upgrade value chains, emphasizing industrialization, technological adoption, and diversification into higher-value coffee products to enhance export revenues and sustainable development.